Sukces firmy a zaangażowanie pracodawców w rozwój ich pracowników - Kust, Izabella (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Continuous skills upgrading and improvement of knowledge by employees is currently the basis of success, and even a determinant of company functioning. Competition, high quality requirements, and the attractiveness of the prices of goods and services, are forcing companies to seek new solutions. The essential element is the need to employ a good employee who meets the requirements of a modern, competitive enterprises functioning in a tough labour market. At the same time phenomena in the surrounding business world, such as financial crisis and political crises have a serious impact on the ability of employers in assisting the employee in its development. Research conducted in July 2014 among graduates and in November 2014 among private university students aimed to analyze the situation in this scope. Students spoke about employers support and its form at the time of studies.
Keywords: absolwenci; kształcenie studentów; pracodawcy; rynek pracy; wspieranie pracownika; wspieranie studenta